Building upcycling or building reconstruction? The ‘Global Benefit’ perspective to support investment decisions for sustainable cities - Fregonara, Elena (Frontiers in Sustainable Cities, 2023)
Investment decisions on demolition and reconstruction vs. refurbishment of the existing building stock can extend beyond financial and economic criteria. However, they must involve energy savings, environmental preservation, material consumption, and waste management for sustainable cities. The regulatory framework used in the past decades and the correlated research seem more unbalanced toward the containment of building energy consumption than toward embodied energy (EE) management in production processes and environmental impact management. Foreshadowing the perspective of a more restrictive regulatory framework on EE, such as prohibiting the displacement of materials with residual energy potential, such as waste in landfills, some challenging frontier issues are involved when facing the limits of the economic evaluation methodologies for transformation projects. Thus, this study aimed to propose a reasoning and an operative modality to support urban governance policies and investment decisions involving private and public subjects in the construction sector. Circular economy and life cycle thinking principles, through life cycle costing (LCC) and life cycle assessment (LCA), are assumed and harmonized with the discounted cash-flow analysis (DCFA): (1) monetizing and modeling into the DCFA the EE and the embodied carbon (EC); (2) internalizing the Global Cost and the new ‘Global Benefit’ into the net present value (NPV) calculation; and (3) focusing on the residual end-of-life value calculation from the early design and investment decision stages. The reasoning can be extended to single buildings, the urban scale, or even entire portions of existing buildings in urban areas concerning typological sub-segments. The operative modality is yet to be explored in a concrete application for orienting urban governance policies and sustainable public–private partnerships, including environmental and, thus, social externalities even in the private real estate investment decision process, in the scope of evolving regulations.